PICTURING THE LOCAL CULTURE: DOCUMENTARY FILMMAKING “BALI BUJA” - Yuliansyah, Virgiawan; Prasetyo Jati, Rocky (Transpublika Publisher, 2021)
The creation of works as a portrait documentary that aims to show the power of statements, the concept of “BALI BUJA” is an association of several art galleries located around Klaten Regency and the outskirts of the Special Region of Yogyakarta. “BALI BUJA” is located in Tlogo Village, Prambanan District, Klaten Regency, Central Java. The formulation of the idea of the creation of this work is to tell a traditional Javanese cultural performance such as music with gamelan or wayang kulit, using the internet as a means of broadcasting. Balibuja has a compulsory song that must be played in every performance. The creation method in this work is conducting research and interviews with relevant parties by using a portrait documentary and ABC resource theory to get a statement that can be trusted and accounted for. The conclusion of this work is a portrait-type documentary work by raising a community that cares about Javanese culture, abbreviated as “BALI BUJA”, by utilizing internet technology as a means of performance.